(untitled) (diségno, 2020)
The scheme of the architectural representation process, and therefore its theoretical basis, is all enclosed, even today, in the famous passage written by Marcus Vitruvius Pollio, the Roman architect of the Augustan era, which takes up and fixes literally, in organic form, a tradition already consolidated for centuries, and not only within the Roman civilization (read more).